2013
DOI: 10.1155/2013/752174
|View full text |Cite
|
Sign up to set email alerts
|

Nonscalpel Vasectomy as Family Planning Method: A Battle Yet to Be Conquered

Abstract: Though nonscalpel vasectomy (NSV) technique was introduced in India in 1992 to increase male participation in family planning, it has failed to get adequate momentum and to achieve its goal. We conducted a cross-sectional questionnaire-based survey to get insight into apathy of men towards NSV. The study included 428 respondents. Most of the respondents (97.4%) were aware of NSV as a method for permanent male sterilization. The majority of them (97.2%) knew that NSV is done without any charge and cash incentiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 5 publications
1
16
1
1
Order By: Relevance
“…Though 68.0% respondents agreed that permanent sterilization is a possible option for them, only 34.1% respondents were willing to adopt NSV as a method of family planning. 18 Similarly, in a study conducted by a Mahat et al majority of respondents accepted vasectomy as the permanent method of contraception while only 45.5% said that sexual functions return to normal following vasectomy. 19 It has been observed that except the domain of condom and permanent methods, female scored higher knowledge as compared with males, however there was no statistically significant difference between the overall knowledge scores (18.67±7.798 vs. 18.41±7.177).…”
Section: Discussionmentioning
confidence: 97%
“…Though 68.0% respondents agreed that permanent sterilization is a possible option for them, only 34.1% respondents were willing to adopt NSV as a method of family planning. 18 Similarly, in a study conducted by a Mahat et al majority of respondents accepted vasectomy as the permanent method of contraception while only 45.5% said that sexual functions return to normal following vasectomy. 19 It has been observed that except the domain of condom and permanent methods, female scored higher knowledge as compared with males, however there was no statistically significant difference between the overall knowledge scores (18.67±7.798 vs. 18.41±7.177).…”
Section: Discussionmentioning
confidence: 97%
“…Garg et al, in their cross-sectional questionnaire-based survey to get insight into apathy of men toward non-scalpel vasectomy, also suggested that circulation of information about family planning by word of mouth is of paramount importance. [3] Tuladhar et al, in their cross-sectional descriptive study of awareness and practice of family planning methods, also concluded that electronic media and friends play a vital role in spreading the awareness. [4] There were 66 out of 81 respondents in our study who were not using contraceptives because of certain reasons; inadequate knowledge and fear of side effects were the most cited reasons for this.…”
Section: Discussionmentioning
confidence: 99%
“…33% said that they think women themselves want to undergo sterilization instead of putting their husband under the knife. 6 However, this decline does not undermine the importance of continued efforts to promote family planning measures 4 and thereby Ministry of health and family welfare, government of India has been promoting family planning programmes in the country. There are number of contraceptive measures/products available under the purview of family planning and all the services are provided free of cost to the population through the public health facilities at the district, block and community levels.…”
Section: Sood a Et Al Int J Reprod Contracept Obstet Gynecol 2014 Jmentioning
confidence: 99%
“…NSV after even being a simple and safe method has failed to achieve its goal. 4 Thus the questionnaire based study was done to get insight of the men about their knowledge and attitude towards various contraceptives methods especially vasectomy and understanding some of the factors influencing the vasectomy acceptance as a contraceptive method.…”
Section: Introductionmentioning
confidence: 99%